Unsteady-state thermal stress and thermal deformation analysis for a pressurizer surge line subjected to thermal stratification based on a coupled CFD-FEM method. (October 2017) - Zhang, Y.; Lu, T.
Highlights: Thermal stresses and thermal deformations are calculated with a coupled CFD-FEM method. The temperature distribution determines the distribution of thermal stress and deformation. The biggish thermal stress is found to occur in the position near the constrained boundary. The maximal total deflection is found to occur in the position far away from the constraints. A method for determining the degree of deformation in the cross-section has been proposed. Abstract: In the pressurizer surge line, the phenomenon of thermal stratification may induce thermal stress and thermal deformation. Excessive thermal stress may result in thermal fatigue of the pipe structure, and excessive thermal deformation may destroy the pipe supports. The phenomenon of thermal stratification, and the induced thermal stress and thermal deformation in the pressurizer surge line would pose a threat on the safe operation of the nuclear power plants (NPPs). Therefore, it is very important to make an analysis to the thermal stratification, thermal stress and thermal deformation of the pressurizer surge line. In this study, a detailed unsteady-state computational fluid dynamics (CFD) analysis involving conjugate heat transfer (CHT) analysis is performed to obtain the transient temperature distributions of the pressurizer surge line under an overall out-surge case, and the thermal loads from the CFD calculations are then transferred to ANSYS Workbench Mechanical as body temperature loads for obtaining the transient thermal stress and the transient thermal deformation. With the coupled computational fluid dynamics-finite element method (CFD-FEM) analysis, the transient response characteristic of the surge line subjected to transient thermal stratification loadings are investigated and analyzed quantitatively. The positions where the maximal thermal stress occurs and where the maximal pipeline displacement occurs are determined, and the method for determining the degree of thermal deformation in the cross-section has been proposed. The coupled CFD-FEM method and the obtained conclusions in this study will be helpful for the design of the pipeline structures and the pipe supports to reduce the structural failure related safety accident.